PENGARUH KEKAYAAN DAERAH, UKURAN PEMERINTAHDAERAH, INTERGOVERNMENTAL REVENUE DAN TEMUAN AUDIT BPK TERHADAP KINERJA PEMERINTAH DAERAH - Gusti Maulana, - (2019)
This study aims to determine the Effect Of Regional Wealth, Regional Government Size, Intergovernmental Reenue, and Audit Finding Of BPK on Local Government Performance. This research using Districts /City in West Java Province as a sample. Sampling technique uses purposive sampling method. Sampling of 81 District/City in West Java Province in 2015 up to 2017. The secondary data of this research is in the form of BPK Examination Report the result of financial statement disclosures. The testing of hypotheses in this research using Analysis Linier Regression Multiple with the program SPSS 23 and the level significance 5 percent. The results of the study in partial shows Regional Wealth does not effect the performance of local government with a significance of 0.481higher than the economic situation of significance specified level 0.05, Regional Government Size does not effect the performance of local government with a significance of 0.096 higher than the economic situation of significance specified level 0.05, Intergovernmental Revenue does significantly on the level of local government with a significance of 0.011 lower than the economic situation of significance specified level 0.05, Audit Finding Of BPK does not effect the performance of local governmence with a significance of 0.351 higher than the economic situation of significance specified level 0.05.